Metabolic stress‐dependent regulation of the mitochondrial biogenic molecular response to high‐intensity exercise in human skeletal muscle. (26th June 2018) - Fiorenza, M.; Gunnarsson, T. P.; Hostrup, M.; Iaia, F. M.; Schena, F.; Pilegaard, H.; Bangsbo, J.
Abstract : Key points: Low‐volume high‐intensity exercise training promotes muscle mitochondrial adaptations that resemble those associated with high‐volume moderate‐intensity exercise training. These training‐induced mitochondrial adaptations stem from the cumulative effects of transient transcriptional responses to each acute exercise bout. However, whether metabolic stress is a key mediator of the acute molecular responses to high‐intensity exercise is still incompletely understood. Here we show that, by comparing different work‐matched low‐volume high‐intensity exercise protocols, more marked metabolic perturbations were associated with enhanced mitochondrial biogenesis‐related muscle mRNA responses. Furthermore, when compared with high‐volume moderate‐intensity exercise, only the low‐volume high‐intensity exercise eliciting severe metabolic stress compensated for reduced exercise volume in the induction of mitochondrial biogenic mRNA responses. The present results, besides improving our understanding of the mechanisms mediating exercise‐induced mitochondrial biogenesis, may have implications for applied and clinical research that adopts exercise as a means to increase muscle mitochondrial content and function in healthy or diseased individuals. Abstract: The aim of the present study was to examine the impact of exercise‐induced metabolic stress on regulation of the molecular responses promoting skeletal muscle mitochondrial biogenesis. Twelve endurance‐trained men performed three cycling exercise protocols characterized by different metabolic profiles in a randomized, counter‐balanced order. Specifically, two work‐matched low‐volume supramaximal‐intensity intermittent regimes, consisting of repeated‐sprint (RS) and speed endurance (SE) exercise, were employed and compared with a high‐volume continuous moderate‐intensity exercise (CM) protocol. Vastus lateralis muscle samples were obtained before, immediately after, and 3 h after exercise. SE produced the most marked metabolic perturbations as evidenced by the greatest changes in muscle lactate and pH, concomitantly with higher post‐exercise plasma adrenaline levels in comparison with RS and CM. Exercise‐induced phosphorylation of CaMKII and p38 MAPK was greater in SE than in RS and CM. The exercise‐induced PGC‐1α mRNA response was higher in SE and CM than in RS, with no difference between SE and CM. Muscle NRF‐2, TFAM, MFN2, DRP1 and SOD2 mRNA content was elevated to the same extent by SE and CM, while RS had no effect on these mRNAs. The exercise‐induced HSP72 mRNA response was larger in SE than in RS and CM. Thus, the present results suggest that, for a given exercise volume, the initial events associated with mitochondrial biogenesis are modulated by metabolic stress. In addition, high‐intensity exercise seems to compensate for reduced exercise volume in the induction of mitochondrial biogenic molecular responses only when the intense exercise elicits marked metabolic perturbations. Key points: Low‐volume high‐intensity exercise training promotes muscle mitochondrial adaptations that resemble those associated with high‐volume moderate‐intensity exercise training. These training‐induced mitochondrial adaptations stem from the cumulative effects of transient transcriptional responses to each acute exercise bout. However, whether metabolic stress is a key mediator of the acute molecular responses to high‐intensity exercise is still incompletely understood. Here we show that, by comparing different work‐matched low‐volume high‐intensity exercise protocols, more marked metabolic perturbations were associated with enhanced mitochondrial biogenesis‐related muscle mRNA responses. Furthermore, when compared with high‐volume moderate‐intensity exercise, only the low‐volume high‐intensity exercise eliciting severe metabolic stress compensated for reduced exercise volume in the induction of mitochondrial biogenic mRNA responses. The present results, besides improving our understanding of the mechanisms mediating exercise‐induced mitochondrial biogenesis, may have implications for applied and clinical research that adopts exercise as a means to increase muscle mitochondrial content and function in healthy or diseased individuals.